Effectiveness of Islamic Education Learning Model Based on Higher Order Thinking Skills (HOTS): Systematic Review - Asnawi, Mohamad Fauzil Adhim; Mas’ad, Zamilul (Progressive Journal of Educational Science, 2025)
This study aims to systematically review the effectiveness of various Islamic Religious Education learning models based on Higher Order Thinking Skills (HOTS). In facing the challenges of the 21st century, higher-order thinking skills are crucial to form critical, creative, and reflective learners. This study examines various HOTS learning models such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), Discovery Learning, Inquiry Learning, Integrative-Conceptual Models, and Digital Learning in the context of PAI. The results of the study show that all of these models consistently improve student learning outcomes from both cognitive and affective aspects. However, its implementation faces several obstacles, especially in teacher readiness, limited facilities and infrastructure, and lack of understanding in HOTS-based assessments. Thus, increasing teacher capacity, strengthening infrastructure, and developing contextual evaluation instruments are urgent matters for optimizing HOTS learning in Islamic Religious Education.